2017
DOI: 10.1186/s12984-017-0330-2
|View full text |Cite
|
Sign up to set email alerts
|

Wireless intraoral tongue control of an assistive robotic arm for individuals with tetraplegia

Abstract: BackgroundFor an individual with tetraplegia assistive robotic arms provide a potentially invaluable opportunity for rehabilitation. However, there is a lack of available control methods to allow these individuals to fully control the assistive arms.MethodsHere we show that it is possible for an individual with tetraplegia to use the tongue to fully control all 14 movements of an assistive robotic arm in a three dimensional space using a wireless intraoral control system, thus allowing for numerous activities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 21 publications
(19 reference statements)
1
41
0
Order By: Relevance
“…Interfaces, which use the remaining capabilities of tetraplegics to generate signals suitable for proportional real-time control, may be based on neural activity [8,9], electromyography (EMG) [10,11], gaze [12], tongue movement [13], or head motion [14,15]. While all these solutions are generally feasible to enable robotic arm control, they might not be accessible to a subset of tetraplegic MS patients, due to the presence of interfering symptoms.…”
Section: Direct Control Interfaces For Tetraplegic Ms Patientsmentioning
confidence: 99%
“…Interfaces, which use the remaining capabilities of tetraplegics to generate signals suitable for proportional real-time control, may be based on neural activity [8,9], electromyography (EMG) [10,11], gaze [12], tongue movement [13], or head motion [14,15]. While all these solutions are generally feasible to enable robotic arm control, they might not be accessible to a subset of tetraplegic MS patients, due to the presence of interfering symptoms.…”
Section: Direct Control Interfaces For Tetraplegic Ms Patientsmentioning
confidence: 99%
“…If the technology is not acceptable for the user, it will not be used. Hence, our design of an exo arm is based on interdisciplinary research into how to advance interaction techniques with tongue control and computer vision [2], how to create flexible and lightweight exos [20] and control systems [47,48], and how to integrate user requirements into the design of the exo arm.…”
Section: The Casementioning
confidence: 99%
“…Assistive technologies aim to increase quality of life [36], reduce dependence on care giver [7] and reduce dependence on the long term care system [8]. Several studies have demonstrated the effectiveness in the use of environment control interfaces (ECI) for environment control or communication through voice commands [9], scan interfaces based on grid structure, eye tracking [10–12] or brain-computer interface (BCI) based on P300 [13], among others.…”
Section: Introductionmentioning
confidence: 99%